PERFORMANCE SKILLS AND ARTISTRY IN SURKHAN OASIS EPIC TRADITIONS - Xakimov Orifjon Boboramazonovich (Journal Park Publishing, 2024)
Folk epics have a special place among the examples of folklore, which are considered the priceless spiritual wealth of our people. This art has been passed from teacher to student from generation to generation directly through live performance. The article discusses performance skills and artistry in the epic traditions of the Surkhan oasis.
Keywords: Genre, folklore performance, art, epic, schools of epic writing, examples of folklore, bakhshi, dombira, poet, centurion.